The recital ebook - Hurwitz, Gregg (Orphan X, 2023)
The Orphan Program—which recruited and trained off-the-books assassins for the government—was responsible for creating some of the world's most dangerous individuals. Evan Smoak, also known as Orphan X, is one of the few still surviving. Josephine "Joey" Morales was the last recruit of the program, now a world-class hacker. Still a teenager, trying to learn how to live as a normal person in the world, she sends Evan on his most unusual mission yet for which he must recruit some of the most elusive and deadly individuals: Candy McClure (Orphan V), Tommy Stojack (black market gunsmith), and Arragón Urea (former drug kingpin). Their help doesn't come free. But Evan will face whatever danger he has to help Joey face her own greatest fears in The Recital .